Carbon nanotubes synthesized by thermal chemical vapor deposition using M(NO3)ndmH2O as catalyst - Yokomichi, H.; Sakai, B.; Ichiharab, M.; Kishimoto, N.
Carbon nanotubes have been synthesized by thermal chemical vapor deposition using catalytic coating of M(NO3)ndmH2O, where M=Al, Mg, Mn, Cu, Zn, Fe, Co, and Ni. The yield of nanotube formation significantly depends on M and can be explained in terms of reducing tendency of the catalysts as well as the catalyst sizes.
Keywords: CARBON NANOTUBES; THERMAL CVD; CATALYST